2021
DOI: 10.1177/1359105321995979
|View full text |Cite
|
Sign up to set email alerts
|

Put MY mask on first: Mothers’ reactions to prioritizing health behaviours as a function of self-compassion and fear of self-compassion

Abstract: Self-compassion predicts mothers’ engagement in health behaviours yet some mothers fear self-compassion. We examined relationships between both self-compassion and fear of self-compassion with mothers’ reactions to prioritizing health behaviours. Mothers rated their self-compassion, fear of self-compassion, read a scenario about prioritizing health behaviours and rated adjectives describing themselves if they behaved as described in the scenario. Self-compassion was positively related to positive reactions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…One qualitative study showed that, whilst participants agreed that self-compassion was beneficial for improving mental health, they also believed it would make them vulnerable and that others would judge them ( Campion and Glover, 2017 ). Recent research has also demonstrated that mothers’ fear of self-compassion can elicit negative reactions when imagining themselves engaging in health behaviours, such as feeling like a failure, irresponsible or careless ( Simpson et al, 2022 ). Given the potential benefits to health and wellbeing for mothers who are breast cancer survivors, future research should examine the impact of the social stigma of cancer and fear of compassion to effectively and sensitively address barriers to self-compassion within this population of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study showed that, whilst participants agreed that self-compassion was beneficial for improving mental health, they also believed it would make them vulnerable and that others would judge them ( Campion and Glover, 2017 ). Recent research has also demonstrated that mothers’ fear of self-compassion can elicit negative reactions when imagining themselves engaging in health behaviours, such as feeling like a failure, irresponsible or careless ( Simpson et al, 2022 ). Given the potential benefits to health and wellbeing for mothers who are breast cancer survivors, future research should examine the impact of the social stigma of cancer and fear of compassion to effectively and sensitively address barriers to self-compassion within this population of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior work suggests that people may not consider being self-compassionate because they hold negative beliefs about self-compassion (Bayir & Lomas, 2016; Chwyl et al, 2020; Kelly et al, 2021; Robinson et al, 2016; Simpson et al, 2022). Specifically, Simpson et al (2022) measured the extent to which participants believed that being self-compassionate would be difficult and then instructed participants to read a hypothetical scenario in which they were self-compassionate before asking them to evaluate this hypothetical self.…”
Section: The Barriers To Being Self-compassionatementioning
confidence: 99%
“…Additionally, prior work suggests that people may not consider being self-compassionate because they hold negative beliefs about self-compassion (Bayir & Lomas, 2016; Chwyl et al, 2020; Kelly et al, 2021; Robinson et al, 2016; Simpson et al, 2022). Specifically, Simpson et al (2022) measured the extent to which participants believed that being self-compassionate would be difficult and then instructed participants to read a hypothetical scenario in which they were self-compassionate before asking them to evaluate this hypothetical self. They found that participants who believed that being self-compassionate would be difficult were more likely to associate their hypothetical self-compassionate self with negative personality traits, such as being insecure, arrogant and careless, as well as negative feelings, such as feeling anxious, unhappy and shameful.…”
Section: The Barriers To Being Self-compassionatementioning
confidence: 99%
“…For example, prior work suggests that some people believe that cultivating a self‐compassionate stance will lower their personal standards, decrease their motivation to grow as a person, and thus fail to achieve their goals (Kelly et al, 2021 ). Additionally, some people may associate being self‐compassionate with negative traits such as weakness, selfishness, irresponsibility, or self‐indulgence (Bayir & Lomas, 2016 ; Campion & Glover, 2017 ; Kelly et al, 2021 ; Robinson et al, 2016 ; Simpson et al, 2021 ). Furthermore, some people may believe that being self‐compassionate goes against the expectations of their family or culture (Bayir & Lomas, 2016 ; Campion & Glover, 2017 ; Gilbert, 2019 ), or that they do not deserve to experience self‐compassion (Gilbert et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%